Development and Validation of UV Spectrophotometric Method for the Estimation of Amlodipine Besylate in Tablets (International Journal of Scientific Research in Science and Technology, 2024)
A rapid, simple, accurate, and specific UV Spectrophotometric method has been developed for the determination of amlodipine besylate in tablets. The spectrophotometric detection was carried out at an absorption maximum of 239 nm using dil. HCl as a solvent. The detector response for the amlodipine besylate was linear over the concentration range of 4-20 µg/ml with a correlation coefficient of 0.999. This method can be adopted in the routine assay analysis of amlodipine besylate and pharmaceutical dosage forms.
Keywords: Amlodipine; Development; Dil; HCl; UV-Visible Spectroscopic method